Eksperimen Pengaruh Layout, Color Scheme, dan Typography dalam Meningkatkan Efektivitas Situs Web Pemerintah di Kota Batam - Li Cen; Rismayana Rismayana; Tony Tan (Politeknik Negeri Lhokseumawe, 2025)
The rapid development of digital governance has positioned government websites as essential tools for delivering information and services to citizens. This study evaluates the effectiveness of official websites of regional government offices (Organisasi Perangkat Daerah/OPD) in Batam City across six indicators: task completion time, user satisfaction, layout, color, typography, and success rate. Data were collected from 135 respondents who were assigned tasks on nine OPD websites, and results were analyzed using descriptive statistics and one-way ANOVA. The findings reveal that while most indicators showed variation among websites, only the success rate differed significantly across OPDs (F = 5.21; p 0.05). Other indicators, including task time, satisfaction, and visual aspects, did not demonstrate statistically significant differences. These results highlight that the ability of users to successfully complete assigned tasks remains the most decisive factor for website effectiveness, while aesthetic elements play a secondary role. The study suggests that standardizing navigation structures and information design across OPD websites could improve user experiences and ensure consistent performance. Future research should expand to include mobile usability and accessibility for vulnerable groups to support inclusive digital public services.